Small innovative business in Russia: regional aspect - Marina Yu. Arkhipova; Kirill V. Arkhipov (Статистика и экономика)
The article is devoted to research of innovative activity of small business in Russia by enterprises clusters depending on the number of employees. Considerable attention is paid to the study of the dynamics and structure of the main indicators, characterizing the available resources and the results of innovative activities, that allows making a number of important conclusions from practical point of view. The analysis has shown that small enterprises, in spite of small scale of innovative activity, operate mostly on new sales channels that help them to ensure product competitiveness on local market. At the same time, competitiveness of small enterprises on global market is significantly higher than the average level for Russia. In their innovative strategies, small businesses mostly focus on the development and modification of products or services over its imitation or total borrowing. The analysis has shown that enterprises with the number of employees from 51 to 70 are leaders to deliver new products on market among small innovative companies. About 10% of the products of this group is new to the world market. Groups of small enterprises with 71-80 employees and up to 20 people are coming next. The share of new products for the global market, made by these enterprises is 5%, which is significantly higher than the national average. These groups of small innovative enterprises are “points of growth” on the innovation effectiveness and competitiveness of products in Russia.The second part presents the study of regional differentiation of small business development in Russia. Multi-dimensional classification helped to divide Russian regions to homogenous groups depending on the development level of small innovative entrepreneurship. The significance of the indicators is proved by using of variance analysis (ANOVA) and calculating of F-statistics values.About 16% of small innovative enterprises are leaders on the resources invested in innovative development, 19% of small innovative enterprises are leading in innovation performance and in the share of innovative products and services in the total volume of the shipped goods. However, approximately 64% of Russia’s regions are characterized by low indices, both resources and results of innovation activity. This is mainly rural, agricultural areas or regions. These regions have medium and large enterprises. The government should develop specific measures to improve the investment climate, innovation infrastructure, as well as institutional reforms for the development of small innovative entrepreneurship in these regions.